Digital nomadism and cities: exploring the production of mobility infrastructures in Barcelona - Alberica Bozzi (Netcom)
This study explores digital nomadism (DN) from the perspective of local service providers. Anchored in the new mobilities paradigm, it aims to explore the territorial impacts of DN in Barcelona, focusing on coworking and coliving businesses. How do service providers perceive digital nomads? How do they adapt their businesses to digital nomads? Three main findings emerge. Firstly, this article pinpoints the importance of shifting the focus from identity of digital nomads to the practice of working remotely while travelling in order to have a more nuanced discussion over the local impacts of DN. Secondly, it presents six adaptation strategies of local businesses and their broader implications for the city, including the emergence of new services, the reconfiguration of the built environment, and ongoing gentrification processes. Thirdly, the study sheds light on the complex interactions between public and private sectors in adapting urban services to digital nomads, often at the expense of the local communities.